Another way to manage supply chains: holonic and multicriteria approach. Issue 3 (13th January 2009) - Mekaouche, Lynda; Ounnar, Fouzia; Pujo, Patrick; Giambiasi, Norbert
Many companies increasingly turn to their core activities to improve their reactivity and to manage their costs. The paper propose a self-organised control of relations between companies in which all the members of a partnership negotiate to guarantee good quality connections between customers and suppliers. Each partner is associated with a decision-making entity named Autonomous Control Entity through which he can evaluate his performance. The integration of the ACEs into a holonic control system is presented. The validation of such a control system for a self-organised logistic partnership network was done through a distributed High Level Architecture simulation environment.